E-READINE S S DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF BERAU DISTRICT IN PROVIDING PUBLIC SERVICES THROUGH THE SI APPLICATION TURTLES DO CHARITY - Ari Ashari; Nina Karlina; Darto Darto (DIA: Jurnal Administrasi Publik, 2025)
This research is about the E-Readiness of the Berau Regency Population and Civil Registration Service in public services using the Si Penyu Beramal application. The research method used is qualitative with a descriptive approach, involving observation, interviews and documentation studies. The results show that electronic readiness is considered sufficient, with several factors influencing it, such as telecommunications infrastructure, connectivity, use of information technology, adequate budget, governing laws, and paradigm changes by employees. The main obstacle is the shift from offline to online systems and the failure to achieve three performance targets. Suggestions include improving infrastructure, human resource training, efficient budget management, and outreach to the community.